Analysis of the role of absorptive capacity in mediating market intelligence and product lifecycle management on business performance at Hewlett-Packard in Bekasi City - Tristan adi; Syarif Noor; Rizky Firmansyah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
This study aims to analyze the effect of Market Intelligence and Product Lifecycle Management on Business Performance, with Progrowth Absorptive Capacity as a mediating variable at Hewlett-Packard in Bekasi City. The study employs a quantitative approach with an explanatory research design. Data were collected through a five-point Likert-scale questionnaire distributed to 489 internal company respondents and then analyzed using Structural Equation Modeling (SEM) based on AMOS. The results show that Market Intelligence has a positive and significant effect on Progrowth Absorptive Capacity and Business Performance, while Product Lifecycle Management does not have a significant effect on Progrowth Absorptive Capacity but has a direct effect on Business Performance. In addition, Progrowth Absorptive Capacity is proven to have a positive and significant effect on Business Performance. Mediation testing indicates that Progrowth Absorptive Capacity partially mediates the effect of Market Intelligence on Business Performance, but does not mediate the effect of Product Lifecycle Management. These findings emphasize the importance of managing market information and absorptive capacity in improving corporate business performance.